TAX MANAGEMENT LEARNING MODEL USING E-INVOICE METHOD - Saragih, Fitriani; Hanum, Zulia; Saripuddin Hsb, Jasman (RADJA PUBLIKA, 2022)
To facilitate the preparation of tax reports, namely providing information to the parties in need that will be used to make comparisons, assess the ability of a company, as well as as a guide for decision making. In order to fulfill the above objectives, tax reports must be comparable. These comparisons can be made in two ways, namely horizontally and vertically. Horizontal comparison is a comparison of a company's tax report with other companies for the same period, which in concept can be easily made if the preparation uses an existing software. This study aims to develop a taxation learning model by using the E-Faktur program as teaching material for lecture materials at universities. The specific target to be achieved in this research is to issue teaching materials in the form of tax books compiled with the E-Faktur program. To achieve this goal, this study uses descriptive analysis to identify the problems that exist in taxation learning at universities at the Muhammadiyah University of North Sumatra (UMSU) in Medan City which has been running so far. These problems include not understanding students in using the E-Faktur program which has been issued for a long time, and not being motivated to study the program due to lack of guidance in carrying out the practice. To find the factors that become obstacles in understanding the use of the program. By identifying these factors, Furthermore, a teaching material can be arranged to motivate students to want to enjoy the teaching material and the goal of educating the nation's children can be achieved. This research was conducted on North Sumatra Muhammadiyah University students who took the 6th semester tax management course for the 2018-2019 academic year. The sample in this study was 90 people. Because of the number of questionnaires that were returned only 90. Based on the data on the questionnaire that has been distributed by the researchers to 90 respondents, obtained data regarding the general description of the research respondents. In this study, the number of female respondents was more, namely 68 people or 75.6%, when compared to male respondents, namely as many as 22 people or 24.4%. This shows that on average the respondents at the Muhammadiyah University of North Sumatra are women. This research was conducted on North Sumatra Muhammadiyah University students who took the 6th semester tax management course for the 2018-2019 academic year. The sample in this study was 90 people. Because of the number of questionnaires that were returned only 90. Based on the data on the questionnaire that has been distributed by the researchers to 90 respondents, obtained data regarding the general description of the research respondents. In this study, the number of female respondents was more, namely 68 people or 75.6%, when compared to male respondents, namely as many as 22 people or 24.4%. This shows that on average the respondents at the Muhammadiyah University of North Sumatra are women. This research was conducted on North Sumatra Muhammadiyah University students who took the 6th semester tax management course for the 2018-2019 academic year. The sample in this study was 90 people. Because of the number of questionnaires that were returned only 90. Based on the data on the questionnaire that has been distributed by the researchers to 90 respondents, obtained data regarding the general description of the research respondents. In this study, the number of female respondents was more, namely 68 people or 75.6%, when compared to male respondents, namely as many as 22 people or 24.4%. This shows that on average the respondents at the Muhammadiyah University of North Sumatra are women. Based on the data on the questionnaire that has been distributed by the researcher to 90 respondents, data is obtained regarding the general description of the research respondents. In this study, the number of female respondents was more, namely 68 people or 75.6%, when compared to male respondents, namely as many as 22 people or 24.4%. This shows that on average the respondents at the Muhammadiyah University of North Sumatra are women. Based on the data on the questionnaire that has been distributed by the researcher to 90 respondents, data is obtained regarding the general description of the research respondents. In this study, the number of female respondents was more, namely 68 people or 75.6%, when compared to male respondents, namely as many as 22 people or 24.4%. This shows that on average the respondents at the Muhammadiyah University of North Sumatra are women.